DAYA SAING TEMBAKAU VIRGINIA LOKAL: ANALISIS RANTAI NILAI - Yudha Hadian Nur; Zamroni Salim (Jurnal Ekonomi dan Pembangunan, 2025)
Virginia tobacco is the main raw material of the Indonesia cigarette industry in Indonesia especially for white cigarettes. The increasing import of Virginia tobacco affected, directly or indirectly, the domestic production. The study analyzes the competitiveness of the local Virginia tobacco. The Value Chain Analysis (VCA) is used to analyze the linkages in the value chain. The data used were collected from field studies conducted in Bojonegoro (East Java) and East Lombok (West Nusa Tenggara). The analysis shows that the local Virginia tobacco has not fully supplied the needs of the domestic cigarette industry due to the limited amount of production, low quality, and supply incontinuity. The length in value chain distribution caused lower quality and price incompetitiveness of local tobacco. The policy of land used – intensification should be pursued to increase the productivity, the quality and the continuous supply of local Virginia tobacco to domestic industry.